ANALISIS PENGALAMAN TAMU TERHADAP HARGA, KUALITAS PELAYANAN, DAN FASILITAS DI HOTEL LABERSA & CONVENTION CENTER SAMOSIR - Norman Simbolon; Dina Octavia (Smart Education, 2026)
Abstract: This study examines guest experiences at Labersa Hotel & Convention Center Samosir regarding price, service quality, and facilities. A qualitative method with a descriptive approach was employed. Primary data were obtained through in-depth interviews and observations of 37 informants selected purposively, while secondary data were gathered from books, journals, and relevant documents. Data analysis techniques included data reduction, data display, and conclusion drawing. The results showed that guest experiences with price were positively perceived, with 86.5% of respondents stating that room rates were in line with the facilities received and 64.9% willing to stay again at the same price. Guest experiences with service quality were rated very positively with a satisfaction level of 84.3%, particularly in terms of complaint handling (94.6%) and staff friendliness (83.8%), although service speed still needs improvement. Guest experiences with facilities showed a fairly positive rating with a satisfaction level of 76.3%, where the most preferred facilities were hotel rooms, swimming pools, and restaurants, yet complaints remained regarding WiFi connectivity, AC conditions, and inconsistent cleanliness. The alignment of price with quality and facilities showed a very positive rating with a satisfaction level of 86.4%. Overall, the average guest satisfaction level reached 81.4%, which falls into the good category. This study concludes that price, service quality, and facilities have provided a satisfying stay experience for guests; however, the hotel needs to improve its facilities, particularly in terms of WiFi stability, AC repairs, and consistent cleanliness standards. Keyword: facilities, guest experience, price, service quality, SERVQUAL Abstrak: Studi ini mengkaji pengalaman tamu di Labersa Hotel & Convention Center Samosir mengenai harga, kualitas pelayanan, dan fasilitas. Metode kualitatif dan deskriptif digunakan. Data primer diperoleh melalui observasi dan wawancara menyeluruh terhadap 37 informan yang dipilih secara purposive, sedangkan data sekunder diperoleh dari buku, jurnal, dan dokumen yang relevan. Teknik analisis data meliputi pengurangan data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pengalaman tamu dengan harga sangat baik; 84,3% responden sangat puas dengan layanan, terutama dengan penanganan keluhan (94,6%) dan keramahan staf (83,8%), dan 64,9% bersedia menginap lagi dengan harga yang sama. Kesesuaian harga dengan kualitas dan fasilitas menunjukkan penilaian yang sangat baik, dengan rata-rata kepuasan tamu 86,4 persen, dan kepuasan umum 81,4 persen. Penelitian ini menemukan bahwa meskipun harga, kualitas pelayanan, dan fasilitas telah memberikan pengalaman menginap yang memuaskan bagi tamu, hotel harus meningkatkan fasilitasnya, terutama dalam hal stabilitas WiFi, perbaikan AC, dan tingkat kebersihan yang konsisten. Kata kunci: fasilitas, harga, kualitas pelayanan, pengalaman tamu, SERVQUAL